Abuse liability of gabapentin in the Saudi population after the pregabalin restriction: A cross-sectional study. Issue 5 (October 2021) - Alkhalaf, Amina A.; Bukhari, Raneem A.; Alshehri, Elham A.; Alshehri, Samah O.; Badr, Aisha F.
الملخص: أهداف البحث: سوء استعمال الأدوية الوصفية موضوع مثير للخلاف والجدل في المملكة العربية السعودية، وذلك بسبب سهولة الحصول على الأدوية من صيدليات التجزئة. تهدف دراستنا إلى تقييم ما إذا كان السكان السعوديون، في جدة، قد استبدلوا تعاطي بريجابالين - أحد الأدوية التي تم تقييدها مؤخرا لصيدليات المستشفيات فقط - إلى جابابنتين. طرق البحث: أجريت دراسة وصفية، وتم جمع وتحليل البيانات خلال شهر واحد، من خلال استبانة تم بناؤها ذاتيا ووُزعت عبر منصات التواصل الاجتماعي. وشملت بنود الدراسة ما يلي: (١) الخصائص الديمغرافية للمشاركين؛ (٢) تاريخ الإدمان (إن وجد)؛ (٣) الاستخدام غير الطبي لجابابنتين (عدد مرات الاستخدام، الاستخدام المتزامن مع أدوية أخرى والمحفزات)؛ و(٤) طريقة اكتشاف الاستخدام غير الدوائي للجابابنتين. النتائج: تم جمع ٣٧٠ مشاركة وكان معظم المشاركين من الإناث ٢٨٩ (٧٨.١٪)، ومعظم أعمار المشاركين دون سن ٣٠ سنة وعددهم ٣٠٠ (٨١.١٪)، وكان لدى ٧٢ (١٩.٥٪) شخصا تاريخ إدمان على الأدوية الوصفية. وكانت أغلب الأدوية التي ورد ذكرها هي بريجابالين ١٧ (٤.٦٪). بالإضافة إلى عدد اللذين أساءوا استخدام جابابنتين ١٠ (٢.٧٪)، حيث أفاد نصفهم (٥) عن سوء استخدام بريجابالين في السابق. معظم مسيئي استخدام جابابنتين قد سمعوا عن تأثيره واستخدامه من الأصدقاء ٨ (٨٠٪) وكان أكثر الأسباب المحفزة للاستخدام هي "قضاء وقت ممتع" ٦ (٦٠٪). وبالإضافة إلى أن نصف مستخدمي جابابنتين قد أجابوا بأنهم يتعاطون الدواء بشكل أسبوعي. الاستنتاجات: سلطت هذه الدراسة الضوء على احتمالية انتقال المسيئي استخدام بريجابالين إلى الجابابنتين. ننصح بتكثيف حملات التوعية لتثقيف كل من المجتمع وصيدليات التجزئة والمجتمعية بشأن هذه المسألة. Abstract: Objective: Following the recently conducted local studies on the growing misuse of pregabalin, Pregabalin misuse has received national attention. These studies have led to the authorities restricting the availability of pregabalin to hospital pharmacies alone. While the recent epidemiological studies and case reports found gabapentin to be misused worldwide, it was previously presumed to be free of any abuse potential. This study assesses the likelihood of there being a diversion to Gabapentin abuse following the Pregabalin restriction in Jeddah, KSA. Methods: A cross sectional observational study was conducted between November 2017 and December 2017 using a self-constructed online survey via Twitter and WhatsApp. The survey items included participants' demographics, additional history, Gabapentin for non-medical use (frequency, concurrent use with other drugs, and motivators), and how the participants knew about the Gabapentin misuse. The data was subjected to a descriptive analysis via the utilization of frequencies and percentages. The analysis was carried out by using SPSS V21. Results: Data of the 370 respondents who took the surveys were collected. Most of the respondents were women (n = 289; 78.1%) and below the age of 30 years (n = 300; 81.1%). A total of 72 respondents (19.5%) had a history of psychoactive drug abuse. Ten of the respondents reported Gabapentin misuse (2.7%). Half of the participants reported prior Pregabalin misuse, and were un-employed. Most of the misusers (n = 8; 80%) came to know about the psychotropic effects of Gabapentin from friends. The most common motives for using it were to 'have fun' and 'peer pressure' (n = 6; 60%). Half of the misusers used Gabapentin on a weekly basis. Conclusion: The findings of our study suggest a potential diversion from Pregabalin to Gabapentin misuse. Regulations and periodic reviews of the psychoactive prescription medications available in the community pharmacies are essential.